2001
DOI: 10.1053/jlts.2001.22460
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic model for early acute rejection after liver transplantation

Abstract: Hepatic graft rejection is a common complication after liver transplantation (LT), with a maximum incidence within the first weeks. The identification of high-risk patients for early acute rejection (EAR) might be useful for clinicians. A series of 133 liver graft recipients treated with calcineurin inhibitors was retrospectively assessed to identify predisposing factors for EAR and develop a mathematical model to predict the individual risk of each patient. The incidence of EAR (<45 days after LT) was 35.3%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 38 publications
4
23
2
5
Order By: Relevance
“…In this series, it did not reach statistical significance, but in other studies, a lower age has been found to be an independent risk factor of rejection (18). This may be the result of immune senescence.…”
Section: Discussioncontrasting
confidence: 88%
“…In this series, it did not reach statistical significance, but in other studies, a lower age has been found to be an independent risk factor of rejection (18). This may be the result of immune senescence.…”
Section: Discussioncontrasting
confidence: 88%
“…El rechazo agudo es una complicación frecuente tras el THO, con una incidencia que varía entre el 40 y el 80% en diferentes series y normalmente se desarrolla en las primeras semanas (6,7,29,30). En nuestro estudio, el rechazo agudo se observó en el 37% de los pacientes, entre los 5 y 15 días tras el trasplante.…”
Section: Discussionunclassified
“…The potential risk of acute rejection must be faced against the benefit of steroid withdrawal. After LTx, HCV infection has been clearly identified as a risk factor for the development of early acute rejection [19] . On the other hand, the presence, number, and treatment of acute rejections were found to be associated with the histologic recurrence of HCV infection after LTx [20,21] .…”
Section: Discussionmentioning
confidence: 99%